Perawatan Metode Kanguru terhadap Kenaikan Berat Badan Bayi - Windi Nur Emiria; Yeni Rustina; Imami Nur Rachmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to provide an overview and ideas from published research results regarding the effectiveness of the kangaroo treatment for weight gain in LBW. The method used is a systematic review using a search strategy on eight electronic databases: Taylor & Francis Online, ProQuest, Semantic Scholar, Scopus, Science Direct, PubMed, EBSCOhost, and Google Scholar. The keywords used in the search were (premature OR